Estimating the impact of universal antiretroviral therapy for HIV serodiscordant couples through home HIV testing: insights from mathematical models. Issue 1 (11th May 2016) - Roberts, Sarah T; Khanna, Aditya S; Barnabas, Ruanne V; Goodreau, Steven M; Baeten, Jared M; Celum, Connie; Cassels, Susan
Abstract : Introduction: Antiretroviral therapy (ART) prevents HIV transmission within HIV serodiscordant couples (SDCs), but slow implementation and low uptake has limited its impact on population‐level HIV incidence. Home HIV testing and counselling (HTC) campaigns could increase ART uptake among SDCs by incorporating couples' testing and ART referral. We estimated the reduction in adult HIV incidence achieved by incorporating universal ART for SDCs into home HTC campaigns in KwaZulu‐Natal (KZN), South Africa, and southwestern (SW) Uganda. Methods: We constructed dynamic, stochastic, agent‐based network models for each region. We compared adult HIV incidence after 10 years under three scenarios: (1) "Current Practice, " (2) "Home HTC" with linkage to ART for eligible persons (CD4 <350) and (3) "ART for SDCs" regardless of CD4, delivered alongside home HTC. Results: ART for SDCs reduced HIV incidence by 38% versus Home HTC: from 1.12 (95% CI: 0.98–1.26) to 0.68 (0.54–0.82) cases per 100 person‐years (py) in KZN, and from 0.56 (0.50–0.62) to 0.35 (0.30–0.39) cases per 100 py in SW Uganda. A quarter of incident HIV infections were averted over 10 years, and the proportion of virally suppressed HIV‐positive persons increased approximately 15%. Conclusions: Using home HTC to identify SDCs and deliver universal ART could avert substantially more new HIV infections than home HTC alone, with a smaller number needed to treat to prevent new HIV infections. Scale‐up of home HTC will not diminish the effectiveness of targeting SDCs for treatment. Increasing rates of couples' testing, disclosure, and linkage to care is an efficient way to increase the impact of home HTC interventions on HIV incidence.